Uma revisão sobre a mecânica quântica em um cenário de comprimento mínimo. - Lemos Filho, Kim Castro (2017)
Quantum theory has shown to be well succeded since its birth at the beginning of the last century. But new ideas that emerged in the physics scenario can change some of quantum mechanics fundamentals, one of these ideas is the existence of a minimun measurable length. In this work we will review the main changes in quantum mechanics arising from the existence of this minimum length.